Bryce Canyon National Park - Petersen, David 1946- (New York Children's Press, 1996)
Describes the history, sights, and facilities of Bryce Canyon National Park in Utah
American Corner
Includes bibliographical references (p. 44) and index
8 11 18
Keywords: National parks and reserves; Bryce Canyon National Park (Utah) -- Juvenile literature